Confirmatory Factor Analysis (CFA) on the Quality of Critical Thinking Instruments, Motivation, and Learning Achievement of Learners - Ragil Dian Purnama Putri; Yeyen Febrilia (Pendagogia: Jurnal Pendidikan Dasar, 2024)
The instrument is said to be valid if the instrument can measure what is to be measured. Type of construct validity using the method confirmatory factor analysis (CFA) with the help of software SPSS. The results of this study say that 15 instrument items consist of critical thinking, motivation, and learning achievement variables, after confirmatory factor analysis (CFA) it can be seen that the variables are grouped into 3 factors. Members of factor 1 are pb1, pb2, pb3, pb4, and pb5. Then those included in the dimension factor 2 are mt1, mt 2, mt ​​3, mt 4, and mt 5. Those included in factor 3 are bk1, bk2, bk3, bk4, and bk 5. So it can be concluded that all items are grouped and have a value loading factor > 0.5 thus all variables are declared valid.